Exploration of the Science of Tajweed in Surah Al-Kahf Presented in Statistics: Eksplorasi Ilmu Tajwid Pada Surat Al-Kahfi yang Disajikan Ke Dalam Ilmu Statistika - Robia Astuti; Khasanah, Binti Anisaul; Nurmitasari, Nurmitasari; Devasari, Putri; Rahmawati, Rizki (Halaqa: Islamic Education Journal, 2022)
This research is motivated by the importance of understanding the science of recitation for every Muslim. This is because the law of reading the Qur'an by paying attention to and obeying the science of recitation is fardhu ain. Exploration of the science of recitation in Al-Kahf's letter into mathematics needs to be done so that students can learn mathematics as well as learn tajwid. This exploration can be presented in statistics for junior high school students where at this age Muslim students must be able to read the Koran with tartil according to the provisions of tajwid. This study aims to explore the science of tajwid (the law of Nun Sukun and Tanwin) in the Al-Qur'an Surah Al-Kahf which will be presented through data presentation techniques with one branch of mathematics, namely statistics. The type of research used in this research is literary research (library). In this study, the approach used is a qualitative approach, namely research conducted by examining existing data sources. The data used include data related to and related to the research theme being studied. Relevant data is collected through literature study or analysis. Methodologically this research belongs to the category of exploratory research, meaning that it explores the science of recitation in Surat Al-Kahf. The result of this research is the presentation of statistical data from the exploration of tajwid, especially on the law of nun mati and tanwin. The results of this study are expected to be a reference for further research to develop teaching materials and learning media for mathematics by integrating the science of recitation in statistical material.